A Technique for Mapping Mathematics Content to Game Design - Vani Kalloo; Permanand Mohan; Dr. Kinshuk (Serious Games Society, 2015)
Research has shown that games can be valuable tools for learning mathematics. In this paper, we explain how we tackled the challenge of mapping mathematics content to games in the design of mathematics learning games. We present a unique technique for mapping mathematics content to game design. The technique can be used to improve the game design process by guiding the designer through one of the more challenging stages of the design process, namely, that of incorporating mathematics content into a game. The technique is based on several factors such as mathematics learning pedagogy, game type categorization, the mathematics curriculum, and past research experience. The technique is unique since it focuses on guiding the game designer through the process of mapping the mathematics content to the game idea. Additionally, the technique incorporates several important game design principles. A preliminary evaluation of the technique was conducted with several amateur game designers. Although there are several limitations of the technique, the evaluation shows that it was useful in helping the game designers to design suitable mathematics learning games.